Anti- N-MethyL-D-Aspartate Receptor Encephalitis in Children Infected with Herpes Simplex - Ni Komang Krisnawati; Ni Kadek Mulyantari; Ni Nyoman Mahartini (Indonesian Association of Clinical Pathologist and Medical laboratory, 2023)
Herpes Simplex Virus (HSV) is a common cause of infectious encephalitis in children, which can lead to severe neurological sequels. There is a new perspective suggesting that herpes simplex encephalitis plays an important role in triggering the synthesis of NMDA receptor antibodies. There have been no data on the incidence of anti-NMDA receptor encephalitis in Indonesia. Herpes simplex encephalitis was found in these patients as a risk factor for anti-NMDA receptor encephalitis. A 9-year-old male patient complained of seizures such as jerking of the right hand and smacking of the lips along with fever for 4 days before being admitted to the hospital. Complaints began with slurred speech and t inability of fingers to hold objects for the previous 8 days. From the physical examination, it was reported that the patient looked seriously ill, blood pressure was 110/80 mmHg, pulse was 117 beats per minute, the temperature was 38.5 C, and respiratory rate was 24 times per minute. Another physical examination was within normal limits. The results of a complete blood count at the time of initial treatment of patients showed mild leukocytosis due to a mild increase in monocytes, whereas blood gas and electrolyte analysis showed hypoventilation at the beginning of hospitalization in which mixed acid-base disturbance, respiratory acidosis, and metabolic alkalosis occurred. Analysis of cerebrospinal fluid in these patients showed mononuclear pleocytosis and the results of immunoserological test in serum indicated HSV1 and HSV2 infection and detected anti-NMDA receptor. Both clinical and laboratory findings in this study supported encephalitis. Herpes simplex virus infection can be a risk factor for patients suffering from anti-NMDA receptor encephalitis.